Resistance to very-long-chain fatty-acid (VLCFA)-inhibiting herbicides in multiple field-selected rigid ryegrass (Lolium rigidum) populations. Issue 3 (11th March 2019) - Brunton, David J.; Boutsalis, Peter; Gill, Gurjeet; Preston, Christopher
Abstract: Five populations of rigid ryegrass ( Lolium rigidum Gaudin) from fields across cropping regions in southern Australia were suspected of having resistance to thiocarbamates, chloroacetamides, and sulfonylisoxazoline herbicides. Resistant (R) populations 375-14, 198-15, 16.2, EP162, RAC1, and A18 and two susceptible (S) populations (SLR4 and VLR1) were included in a dose–response study. All suspected R populations expressed resistance to one or all herbicides (thiocarbamates, chloroacetamides, and pyroxasulfone). Population 198-15 exhibited the highest LD50 to triallate (44.7-fold), prosulfocarb (45.7-fold), S -metolachlor (31.5-fold), and metazachlor (27.2-fold) compared with the S populations. Populations 198-15 and 375-14 were also resistant to pyroxasulfone (13.5- and 14.9-fold) compared with the S populations, as was population EP162. This study documents the first case of field-evolved resistance to thiocarbamate, chloroacetamide, and sulfonylisoxazoline herbicides in L. rigidum .